Khatlon region’s agriculture sector development trends - Khakimov, Parviz; Ashurov, Timur (International Food Policy Research Institute, 2025)
This study examines recent agriculture sector development trends in Khatlon region of Tajikistan and its contribution to development of the sector between 2010 and 2021. The findings of the study show that the development of the crops sector in the region was strongly intensive, except sluggish intensive growth for cotton and extensive growth for potato. Further deep dive is needed to figure out the source of growth, however, lack of disaggregated data prevents us from doing so in this analysis. To understand the drivers of recent growth the farmers survey needs to be conducted. Unlike the crop sector, the livestock sector in Khatlon region has experienced mainly extensive growth, with surge up in cattle and small ruminants’ population rather than productivity increase. The livestock sector faces several challenges such as severe degradation of pastures due to poor pasture management system, and increased pressure on pasture due to rapidly growing livestock numbers. In addition, the sector is affected by climate change and at the same time accelerates the ongoing process of climate change due to greenhouse gases, especially methane emissions. In sum, the region now plays a vital role in meeting Tajikistan's food security needs and income generation for rural households, however, further sustainable growth of the sector requires addressing challenges, increasing investments into the sector and promoting CSA practices (Table 1A in Appendix).